Prevalence, Etiology, and Risk Factors of Mastitis in Dairy Cattle in Embu and Kajiado Counties, Kenya - Christine M. Mbindyo; George C. Gitao; Charles M. Mulei (Veterinary Medicine International)
Bovine mastitis continues to be a leading cause of heavy economic losses in the dairy industry and a public health hazard globally. This cross-sectional study investigated the prevalence, etiologies of clinical and subclinical mastitis, and associated predisposing factors in Embu and Kajiado counties in Kenya. A semistructured questionnaire was administered to 154 smallholder dairy farmers to collect data on management practices, animal factors, and disease history. A total of 395 dairy cows were initially screened for subclinical mastitis using the California mastitis test (CMT), and milk samples were aseptically collected. Both CMT positive and CMT negative samples were analyzed using conventional bacteriological isolation and identification procedures. In the present study, the overall prevalence of mastitis based on CMT and clinical examination was 80% (316/395), out of which 6.8% (27/395) was clinical mastitis, while 73.1% (289/395) was subclinical mastitis. Based on culture, the overall prevalence of clinical and subclinical mastitis was 51.6% (815/1580), 74.4% (294/395), and 76.6% (118/154) at the quarter, cow, and farm level, respectively. From the 1574 milk samples analyzed by cultured, 1016 bacteria were yielded. The predominant bacteria were coagulase-negative Staphylococcus (CNS), 42.8% (435/1016), and in decreasing order, Streptococcus species, 22.2% (226/1016), Staphylococcus aureus, 15.7% (160/1016), and Pseudomonas aeruginosa, 5.1% (52/1016), and the least was Enterobacter species, 0.7% (7/1016), while 23.7% of the sample yielded no bacterial growth. Risk factor analysis revealed that milking mastitic cows last (p=0.002), using a clean udder drying towel for each cow (p=0.033) and previous history of mastitis (p=0.046) were significantly associated with presence of mastitis. The current study has shown a relatively high prevalence of subclinical mastitis with CNS as predominant bacteria. Therefore, control measures are urgently warranted. Management factors such as milking mastitic cows last, using a clean towel for udder drying for each cow, and culling mastitic cows should be considered and included in the Kenyan mastitis control programs.